Uji Daya Hambat Trichoderma spp. Isolat Kabupaten Kapuas Kalimantan Tengah Terhadap Collettotrichum spp. pada Cabai - Jabbarsyah I Lubis; Yusriadi Yusriadi; Akhmad Rizali (Agroekotek View, 2018)
This study aims to determine the inhibition power of Trichoderma spp. isolate of Kapuas Regency, Central Kalimantan to Colletotricum spp. And to know the difference in the ability to inhibit Trichoderma spp., Based on the location of the soil (rice field, moor and pepper crops) in Kapuas District. Trichoderma spp capability testing against Colletotrichum spp. performed on PDA media, with a double culture technique, ie by growing in pairs Trichoderma spp and Colletotrichum spp. Based on the data of the analysis of variance, the applied treatment did not give effect to the percentage of pathogen resistance of Colletotrichum spp., But Trichoderma spp. of various isolates were able to inhibit Colletotrichum spp. percentage of inhibition of Colletotrichum spp. the smallest is in the application of Trichoderma spp. isolate soil location B (TCSB) and then followed by Trichoderma spp. field A soil isolates (TCSA). While the percentage of inhibition of Colletotrichum spp. the largest is in the application of Trichoderma spp. soil isolates of B (TCCB) chili plants followed by Trichoderma spp. chili plant ground isolate A (TCCA).